From Tradition to Innovation: Economic Transformation and Women’s Empowerment in Pusong Lama Fishing Village - Mujiburrahman, Mujiburrahman; Chalid, Ibrahim; Suadi, Suadi; Riski, Aflia; Fadillah, Siti; Elsa, Rima (Andalas International Journal of Socio-Humanities, 2025)
This study explores the economic transformation of coastal fishing households in Pusong Lama village, Lhokseumawe, Aceh, from traditional fishing practices to creative, value-added production. Using a qualitative approach supported by observation, interviews, and focus group discussions, the research analyzes how local initiatives and women’s participation have redefined livelihoods through the processing of keumamah (dried tuna) into marketable creative products. Data were analyzed using the interactive model of Miles and Huberman, encompassing data reduction, display, and conclusion drawing. The findings reveal that the creative economy movement not only increases household income but also fosters social empowerment, particularly among women who now manage production, marketing, and financial activities. Despite these achievements, challenges remain in terms of raw material availability, price fluctuations, and limited marketing access. This study contributes to the growing discourse on sustainable coastal development and women’s economic empowerment by showing how traditional fishing communities can adapt to market-oriented innovation through creative industry models.